IMPLEMENTATION STATUS OF K12 SOCIAL STUDIES PROGRAM IN PHILIPPINE PUBLIC SCHOOLS - Rogayan, Danilo V Jr.; Villanueva, Efreign Earl N (PEOPLE: International Journal of Social Sciences, 2019)
Curriculum implementation needs to be gauged regularly to ensure its effectiveness, efficiency and its relevance to the needs of the students and of the industry. This descriptive-survey research gauged the status of the Social Studies program under the K12 Curriculum for its first four years of implementation. A total of 30 Social Studies teachers and 5 school administrators from three national secondary schools in one division in Central Luzon, Philippines served as respondents of the study. Results revealed that a typical teacher is a female, 37.33 years old, teaching profession for 3.07 years, and a college graduate while a typical administrator is a female, 32.20 years old, serving for about 21.60 years, and a college graduate with MA units. The secondary teachers and school administrators assessed the status of implementation of the curriculum in selected public secondary schools as “moderately observed” in terms of resource variables (M=3.63), process variables (M=3.84) and contextual variables (3.93). Moreover, there is no significant difference between the assessment of the teachers and administrators on the status of the implementation of Social Studies program with regard to the three components. Further, there is no significant difference in the assessment of the teachers and administrators when respondents are grouped according to profile variables. A well-monitored implementation of the K12 Curriculum, specifically the Social Studies program, by stakeholders is recommended. Periodic assessment of the curriculum may also be done to ensure its alignment to the changing educational landscapes and to cope with the challenges of Education 4.0.